2023
DOI: 10.1186/s10194-023-01572-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in primary headache disorders: a systematic review and meta-analysis

Abstract: Background The role of inflammation and cytokines in the pathophysiology of primary headache disorders is uncertain. We performed a systematic review and meta-analysis to synthesise the results of studies comparing peripheral blood cytokine levels between patients with migraine, tension-type headache, cluster headache, or new daily persistent headache (NDPH), and healthy controls; and in migraine between the ictal and interictal stages. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 75 publications
0
14
1
Order By: Relevance
“…This proinflammatory cytokine has been involved in pathological processes underlying chronic pain conditions such as new daily persistent headache 45 and migraines. 46 Noteworthy, we previously showed that ΤΝFα is positively correlated with sTREM2 in CSF. 15 It remains to be further determined whether increased TNFα in chronic pain induces microglial activation or whether TNFα is produced by chronic painactivated microglia.…”
Section: Discussionmentioning
confidence: 92%
“…This proinflammatory cytokine has been involved in pathological processes underlying chronic pain conditions such as new daily persistent headache 45 and migraines. 46 Noteworthy, we previously showed that ΤΝFα is positively correlated with sTREM2 in CSF. 15 It remains to be further determined whether increased TNFα in chronic pain induces microglial activation or whether TNFα is produced by chronic painactivated microglia.…”
Section: Discussionmentioning
confidence: 92%
“…Even though MOH is commonly seen in migraine patients and various studies have focused on proinflammatory cytokines in migraine, a link between inflammation and leaky gut has not been investigated in MOH patients. In a recent meta-analysis, IL-6, IL-8, IL-1β, and tumor necrosis factor α were the proinflammatory cytokines implicated in migraine patients [ 22 ]. The role of the gut-brain axis in migraine headache has already been suggested in several papers [ 23 ] and different gut microbiome profiles were reported in episodic and chronic migraine patients, and healthy controls [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…NDPH can be characterized by migraine-like headaches, and sometimes it is difficult to distinguish between the two disorders. Elevated levels of the pro-inflammatory cytokines IL-6, IL-8, and TNF-α are commonly observed in patients with migraine [ 26 ]. Although the etiology of NDPH is not fully understood, previous clinical evidence suggested that infection and inflammation may be important predisposing factors for NDPH [ 27 ].…”
Section: Discussionmentioning
confidence: 99%